DERMATOMYCOSES AND METHODS OF LABORATORY DIAGNOSIS - Egamberdi E. Eshboev; Otabek S. Imamov; Normurod D. Djumaev; Indira N. Abduvakhitova; Gayrat Sh. Toxtayev (Central Asian Journal of Medicine, 2023)
The purpose of the study: preparation of a cheap and high-quality fresh medium, the basis of which is made up of local ingredients for the growth of pathogenic fungi. Materials and research methods: in the process of carrying out scientific research work, pathological material from 400 patients (skin scraping, damaged hair fiber, and nail plates) was studied in the Saburo food environment, which is applicable to the causative agents of fungal diseases of the skin, and in the proposed food environment. The results: cheap and high-effective medium was created for use in the daily practice of bacteriological laboratories under all treatment (dispensaries of venereal diseases, private laboratories) institutions located in the territory of the Republic.